EVALUASI MANFAAT OLAHRAGA JALAN SANTAI TERHADAP KESEHATAN FISIK DAN MENTAL DI THEOLOGIA SURYA NUSANTARA TAHUN 2017 - Pipin Sumantrie (Elisabeth Health Jurnal, 2018)
Health is a very valuable capital, awareness of the value of this increasing adult health, where a lot of people willing to spend a huge amount of money to gain health.One of getting health care is to execute the exercise, the type of sports that are easily and safely recommended to all people, that sports a relaxing stroll.Because to do this kind of exercise does not require special skills and talents, as well as the usual done by everyone, both kids up to parent Methods: this research is a descriptive approach using correlation through measurement /hubungan Association (measures of association).As for the sample in this research is the Theological students Surya Nusantara Pematangsiantar with engineering Acidential the sample amounted to 20 people. Results: from the research found that the physical for the respondents who "walk" with a value of significan sistol 0.03, 0.01, 0.00 pulse diastol.And "rarely relaxed way" with a value of significan sistol 0.05, 0.03, 0.02 pulse diastol.And the resulting percentage to mental "rarely" with a value of percentage of 61.5%, and on the respondents who "often" with a value of percentage of 96.4%, thus found the presence of sports influence stroll against the physical and mental health. Conclusion: health is one of the main factors that affect the fitness of body and appearance, as well as the most valuable treasure that never exchanged by anything, then it is recommended to people to set aside time to do the motion body by doing sports a relaxing stroll.Because in a healthy body there is a healthy soul.